A influência do ciclo menstrual na vida escolar segundo discentes de uma escola pública estadual de Bragança (PA) - XAVIER, Williane da Silva (2023)
This research adopted a qualitative approach regarding the multifaceted challenges experienced by individuals who menstruate as perceived by elementary school students in their final years. The study involved data collection through conversational circles, collated via two audio recorders, the methods ware applied right after a documentary and illustrative materials exhibition showing the various phases of the menstrual cycle, all data collection were facilitated by two mediator researchers. Seven students, comprising five individuals who menstruate and two who do not, participated in this study. Data analysis was made by transcriptions, meticulous reading, categorization, and a critical interpretative analysis of the statements arising from the conversational circles. The theoretical background for this study draws from UNFPA, UNICEF (2021), Lins, Machado, Escoura (2016), Weeks (2003), Brasil (2021), Pará (2021). The findings of our investigation revealed that the challenges faced by individuals who menstruate transcend the mere absence of sanitary products; these challenges also involve various aspects of their lives, encompassing educational, familial, social, and self-awareness. Our data revealed concerns regarding the inadequate discourse surrounding bodily changes, the insufficient infrastructure within educational institutions for the promotion of menstrual hygiene, the interpersonal and familial repercussions of menstruation, the declining age of menarche, and the students limited understanding of their own bodies. In summation, it is evident that the challenges confronted by individuals who menstruate within the school environment have a direct impact on their academic performance, inciting apprehensions, distress, and negative feelings related to menstruation, drawing attention to a fundamental issue concerning menstruation and the lack of attention within the educational environment.